Ovarian carcinoma : etiology, diagnosis, and treatment - Barber, Hugh R. K (Springer, 1993)
Now in its third edition! Ovarian Carcinoma is an invaluable source of information because it gives a complete overview of all aspects: histologic classification, FIGO staging, tumor markers, symptoms, diagnosis, operative treatment, chemotherapy, radiation therapy, complications such as pregnancy and AIDS, biological response modifiers and the status of clinical trials. The new chapter on biologic response modification is especially noteworthy since it reports on new developments now being tested in clinical trials. All the other chapters have been expanded and updated, too. At the same time, the author has kept his clear, readable style that makes the book easy to understand. The contents are based on actual clinical experience and thus extremely practical.
Keywords: gynekologie a porodnictví; onkologie; vaječníky - rakovina - etiologie - diagnostika - terapie chirurgická - technika - příručky